HUBUNGAN ANTARA PENGETAHUAN DENGAN KEPATUHAN KONSUMSI TABLET FE TERHADAP KEJADIAN ANEMIA PADA IBU HAMIL DI PUSKESMAS PEKANBARU KOTA - Fitri Fitri; Jerika Jerika; Yuliana Arsil; Irma Susan Paramita (NUTRIENT, 2021)
Mother's knowledge is very in fluential on the nutrition of the baby it contains and also the pattern of food consumption, especially foods containing iron, because if iron deficiency during pregnancy in a relatively long time will cause anemia. Consumption of iron tablets is strongly influenced by the awareness and compliance of pregnant women. The purpose of this study was to examine the relationship between knowledge and compliance in the consumption of Fe tablets in pregnant women at the Pekanbaru City Health Center. This type of research is descriptive research, with a cross sectional design. The population in this study were pregnant women in the third trimester in the work area of the Pekanbaru City Health Center. The sample size was 30 pregnant women. The sampling method used purposive sampling technique. For variables, namely knowledge of pregnant women, compliance with Fe tablet consumption and hemoglobin levels of pregnant women. Bivariate data analysis using chi- square test. The result of this study indicate that there is no relationship between maternal knowledge and adherence to Fe tablet consumption and also there is no relationship between adherence to Fe tablet consumption and the incidence of anemia in the Pekanbaru City Health Center area.